Role of Ethylene Biosynthesis Genes in the Regulation of Salt Stress and Drought Stress Tolerance in Petunia - Naing, Aung Htay; Campol, Jova Riza; Kang, Hyunhee; Xu, Junping; Chung, Mi Young; Kim, Chang Kil (Frontiers in Plant Science, 2022)
Ethylene plays a critical signaling role in the abiotic stress tolerance mechanism. However, the role of ethylene in regulating abiotic stress tolerance in petunia has not been well-investigated, and the underlying molecular mechanism by which ethylene regulates abiotic stress tolerance is still unknown. Therefore, we examined the involvement of ethylene in salt and drought stress tolerance of petunia using the petunia wild type cv. “Merage Rose” and the ethylene biosynthesis genes (PhACO1 and PhACO3)-edited mutants (phaco1 and phaco3). Here, we discovered that editing PhACO1 and PhACO3 reduced ethylene production in the mutants, and mutants were more sensitive to salt and drought stress than the wild type (WT). This was proven by the better outcomes of plant growth and physiological parameters and ion homeostasis in WT over the mutants. Molecular analysis revealed that the expression levels of the genes associated with antioxidant, proline synthesis, ABA synthesis and signaling, and ethylene signaling differed significantly between the WT and mutants, indicating the role of ethylene in the transcriptional regulation of the genes associated with abiotic stress tolerance. This study highlights the involvement of ethylene in abiotic stress adaptation and provides a physiological and molecular understanding of the role of ethylene in abiotic stress response in petunia. Furthermore, the finding alerts researchers to consider the negative effects of ethylene reduction on abiotic stress tolerance when editing the ethylene biosynthesis genes to improve the postharvest quality of horticultural crops.